Structure and stress state of TiN and Ti₀.₅₋xAl₀.₅YxN coatings prepared by the PIII&D technique from filtered vacuum-arc plasma - Reshetnyak, E.N. (Вопросы атомной науки и техники, 2014)
The results of investigations of the structure and stress state of TiN and Ti₀.₅₋xAl₀.₅YxN coatings deposited from the filtered vacuum-arc plasma under high voltage pulsed bias potential on the substrate are presented. It was found that axial texture [110] is formed in coatings when pulses potential with an amplitude 0.5…2.5 kV are applied. For TiN coatings with increasing amplitude of the potential the perfection of texture is increased and the level of residual compressive stress is decreased. As for Ti₀.₅₋xAl₀.₅YxN coatings with increasing amplitude the stress level is increased. In this case the texture is most strong outlined at the amplitude of 1 kV. With further increase in the amplitude the texture perfection becomes weaker. Differences of structure and stress state may occur due to the possibility of phase transition for multi-component coatings Ti-Al-Y-N associated with the decay of the supersaturated solid solution (Ti,Al)N stimulated by high energy ion bombardment.